Moderating role of self-construal on relationship of intercultural sensitivity with informal and formal cross-nationality diversity engagements - Yunus, Norzita (2017)
Intercultural sensitivity, the affective dimension of intercultural communication competence, is paramount in enabling people to effectively participate in an increasingly pluralistic society. Past studies have shown that positive interaction with culturally different others contribute to a number of positive outcomes. Despite the importance of intercultural sensitivity, very limited studies have examined its relationship with engagement in informal and formal cross-nationality diversity within institution of higher learning settings particularly in the non-Western and non-American contexts. Framed upon Allport’s Contact Theory, the present study examined the relationship of informal and formal cross-nationality diversity engagement with intercultural sensitivity among local undergraduate students in selected universities in Malaysia. It also examined the role of self-construal, an assumed moderator, in the relationship of engagement in informal and formal crossnationality diversity engagement with intercultural sensitivity. Using self-administered questionnaires, 1000 local undergraduate students from three universities participated in a cross-sectional survey. Since many Malaysian universities are heterogeneous in terms of student racial composition, stratified sampling was used to ensure representativeness of sample. Informal crossnationality diversity engagement is defined as voluntary engagement in interaction with people who are culturally distinct within informal, unstructured settings. Formal cross-nationality diversity engagement is defined as engagement in diverse activities that provide knowledge on cultural others within formal, structured settings. All variables were measured using Likert’s 5-point item scale, except for self-construal which was measured using Likert’s 7-point item scale. All variables were tested for validity and reliability in a pilot test prior to the field data collection. At bivariate level, Pearson’s correlation analysis was applied to test the hypothesized relationships of informal and formal diversity engagement with intercultural sensitivity. The findings revealed that both informal and formal cross-nationality diversity engagement are significantly and positively related with intercultural sensitivity. However, the strength of the relationship for both was weak. To determine the contribution of informal cross-nationality diversity engagement and formal cross-nationality diversity engagement towards intercultural sensitivity, a multiple regression was applied. Gender, ethnicity and experience going for vacation abroad were included as control variables. Interestingly and surprisingly, it was found that the formal cross-nationality diversity engagement had a significant positive correlation with intercultural sensitivity while the informal cross-nationality diversity engagement had a negative significant correlation with intercultural sensitivity. Further, the findings revealed that formal cross-nationality diversity engagement was the strongest predictor variable. The five variables, which are informal cross-nationality diversity engagement, formal cross-nationality diversity engagement, gender, ethnicity and experience going for vacation abroad, accounted for a small variance of intercultural sensitivity. A hierarchical regression analysis was performed to test the hypothesized moderating role of self-construal on the relationship of informal and formal crossnationality diversity engagement with intercultural sensitivity. When self-construal was added in the regression analysis, the analysis revealed different pattern of findings. Self-construal was found significantly positively correlated with intercultural sensitivity, and there was an interaction effect of self-construal on the positive relationship of formal and informal diversity engagement with intercultural sensitivity. The findings suggest that the contribution of formal and informal crossnationality diversity engagement on intercultural sensitivity is more pronounced among students with low interdependence than among students with high interdependent self-construal. All in all, both informal and formal cross-nationality diversity engagements are significant but not strong predictors of intercultural sensitivity. The theoretical contribution of the study lies in advancing understanding by clarifying the role of self-construal within the aforementioned relationship, which has not been examined before. Informal and formal diversity engagement has differential influence on intercultural sensitivity development depending on one’s degree of interdependent self-construal. In terms of practical implication, drawing on the findings on positive role of formal and informal diversity engagement on students’ intercultural sensitivity development, it is suggested that Malaysia higher education institutions should systematically and actively promote and enhance students’ engagement in culture-related diversity, particularly among students with low interdependent self-construal.